Alteration of lung diffusion capacity in IgA nephropathy. Issue 3 (March 1996) - Ravilly, S; Chaussain, M; Iniguez, J L; Lenhert, A; Kalifa, G; Brun, P; Niaudet, P; Gendrel, D
Abstract : OBJECTIVE: To establish whether changes of lung transfer for carbon monoxide (TLCO) are related to the phase of IgA nephropathy. METHODS: Respiratory function was tested in 12 children with IgA nephropathy assessed by percutaneous renal biopsy. This was done during acute exacerbations or haematuria-free phases of the disease. RESULTS: TLCO was low in 12/13 measurements made in the haematuric phase of IgA nephropathy or during the month following gross haematuria (mean TLCO 64% of expected values). Lung volumes and blood gas values were normal and only minor radiological signs of interstial lung involvement were observed in 11/12 patients. When respiratory tests were performed more than three months after gross haematuria, TLCO was low in 4/9 patients, with no relation to the significance of residual proteinuria or severity of findings at renal biopsy. There was a significant difference between tests performed when haematuria was present or recent and those performed more than three months after an episode of gross haematuria (p < 0.01). CONCLUSIONS: The decrease of TLCO in the acute phases of the disease is probably related to alterations of the lung alveolarcapillary membrane by immune complexes containing IgA. This non-invasive technique, easy to perform and repeat, could be of value in the diagnosis of IgA nephropathy in haematuric children.